Hematological Parameters in Patients with Pulmonary Tuberculosis and its Presentation among Favorable and Unfavorable Treatment Outcomes - S. Ramesh Kumar; Chandrasekaran Kandhasamy; V. Banurekha Velayutham; Ponnuraja Chinnaiyan; Muthuramalingam Kannan; M. S. Jawahar; C. Padmapriyadarsini (Wolters Kluwer Medknow Publications, 2024)
Background: Tuberculosis (TB) management continues to be a challenge globally; weakened immunity plays a significant role in the reactivation of TB. There is limited information on hematological parameters in patients with pulmonary TB and its association with outcome. Objectives: We present hematological parameters of newly diagnosed sputum-positive pulmonary TB patients enrolled in a randomized, clinical trial that assessed the efficacy and safety of 3 and 4 regimens using moxifloxacin. Materials and Methods: Blood hematological parameters at baseline, comparison of the baseline and end of treatment values, including the monocytes by lymphocytes ratio (M/L), neutrophil lymphocyte ratio (N/L), and platelet lymphocyte ratio (P/L) between the patients with favorable and unfavorable TB treatment outcome, and among different age group and sex presented in this paper. Results: Among the total 1059 patients, 782 were males, the mean hemoglobin (HB) ± standard deviation (SD) was 11.5 g/dL ± 2.0, the mean white blood cell (WBC) count ± SD was 9800 ± 3009 and the mean platelet count (in lakhs) ± SD was 4.24 ± 1.42 cells/uL. There was an increase from baseline in the mean hemoglobin, eosinophil, and lymphocyte count and a decrease in mean neutrophil, monocyte counts to the end of treatment. There was a decrease in baseline mean total WBC count posttreatment, both in favorable (10,271 cells/uL ± 3007 SD to 6689 cells/uL ± 1837 SD, [P ≤ 0.001]), and unfavorable TB outcome patients. Conclusion: An increase in HB, and a decrease in WBC count, M/L, N/L, and P/L ratio is possible at the end of TB treatment and future studies to correlate blood hematology parameters with TB treatment outcome.